Factorise: x^2 – 4ax – b^2 + 4a^2 = 0​

Question

Factorise:
x^2 – 4ax – b^2 + 4a^2 = 0​

in progress 0
Reagan 3 months 2021-11-10T20:10:56+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-10T20:12:14+00:00

    Answer:

     {x}^{2}  - 4ax -  {b}^{2}  + 4 {a}^{2}  \\  = ( {x}^{2}  - 4ax + 4  {a}^{2} ) -  {b}^{2}  \\  = (( {x}^{2}) - 2(x)(2a) + ( {2a)}^{2}  ) -  {b}^{2}  \\   = ( x - 2a - b)(x - 2a - b)

    HOPE IT HELPS YOU ✌️

    PLEASE MARK ME AS BRAINLIST

    0
    2021-11-10T20:12:25+00:00

    Answer:

    Hey here’s your answer.

    Step-by-step explanation:

    X^2-4ax+4a^2-b^2=0

    x^2-2*2a*x+(2a)^2-(b)^2=0

    (x-2a)^2-(b)^2=0

    (x-2a-b)(x-2a+b)=0

    x-2a-b=0 x-2a+b=0

    x=b+2a x=2a-b

    Therefore, x= 2a+b or 2a-b

Leave an answer

Browse

14:4+1-6*5-7*14:3+5 = ? ( )